2017
DOI: 10.18632/oncotarget.14862
|View full text |Cite
|
Sign up to set email alerts
|

Selective extracellular vesicle exclusion of miR-142-3p by oral cancer cells promotes both internal and extracellular malignant phenotypes

Abstract: Packaging of small molecular factors, including miRNAs, into small extracellular vesicles (SEVs) may contribute to malignant phenotypes and facilitate communication between cancer cells and tumor stroma. The process by which some miRNAs are enclosed in SEVs is selective rather than indiscriminate, with selection in part governed by specific miRNA sequences. Herein, we describe the selective packaging and removal via SEVs of four miRNAs (miR-142-3p, miR-150-5p, miR-451a, and miR-223-3p) in a panel of oral dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 75 publications
0
71
0
Order By: Relevance
“…Cancers are far more complex than realized due to the genetically heterogeneity, which involve with the protean miRNA and long ated with increased vascular density in vivo. 18 We here found that miR-142 was significantly reduced during the development of HCC and TGFβ could be targeted to inhibit the cell vitality, proliferation,…”
Section: Discussionmentioning
confidence: 69%
“…Cancers are far more complex than realized due to the genetically heterogeneity, which involve with the protean miRNA and long ated with increased vascular density in vivo. 18 We here found that miR-142 was significantly reduced during the development of HCC and TGFβ could be targeted to inhibit the cell vitality, proliferation,…”
Section: Discussionmentioning
confidence: 69%
“…MiRNAs are ~22 nucleotide transcripts that modulate gene expression at the post-transcriptional level (Bartel 2004). Although the functional importance of EV-miRNAs as signaling molecules has received some support, including in immunologic response and metastatic tumor cell growth (Mittelbrunn et al 2011; Montecalvo et al 2012; Pegtel et al 2010; Fong et al 2015; Dickman et al 2017; Zhou et al 2014; Tominaga et al 2015; Hsu et al 2017), the molecular mechanisms and regulation of sorting miRNAs into EVs remain poorly understood. Both non-selective (Tosar et al 2015) and selective (Shurtleff et al 2016; Santangelo et al 2016; Villarroya-Beltri et al 2013) mechanisms of miRNA sorting into EVs have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of single miRNAs showed higher abundance in cCM than in sEVs and only 9 of the analyzed miRNAs showed >50% signal coming from sEVs. miR-142-3p (80% sEV signal), was recently shown by another group to be selectively packaged in sEVs by a panel of oral squamous cell carcinoma cell lines, which resulted in lower intra-cellular levels and promoted malignant changes in these cells via increase of TGFBR1 expression 47 .…”
Section: Discussionmentioning
confidence: 99%